2022
DOI: 10.1007/s40615-022-01274-x
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Level of Care and Outcomes Among Patients with COVID-19: Associations Between Race/Ethnicity, Social Determinants of Health and Virtual Hospitalization, Inpatient Hospitalization, Intensive Care, and Mortality

Abstract: Objective To examine the role of race/ethnicity and social determinants of health on COVID-19 care and outcomes for patients within a healthcare system that provided virtual hospital care. Methods This retrospective cohort study included 12,956 adults who received care for COVID-19 within an integrated healthcare system between 3/1/2020 and 8/31/2020. Multinomial models were used to examine associations between race/ethnicity, insurance, neighborhood deprivation measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…The characteristics of the included studies are shown in Table 1 . Four studies were conducted in the USA ( 19 , 21 , 24 , 27 ), five in the UK ( 22 , 23 , 26 , 28 , 29 ), one in New Zealand ( 20 ), and one in Canada ( 25 ). The sample sizes ranged from 964 (conducted in Canada) to 2,311,282 (conducted in UK) ( 25 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the included studies are shown in Table 1 . Four studies were conducted in the USA ( 19 , 21 , 24 , 27 ), five in the UK ( 22 , 23 , 26 , 28 , 29 ), one in New Zealand ( 20 ), and one in Canada ( 25 ). The sample sizes ranged from 964 (conducted in Canada) to 2,311,282 (conducted in UK) ( 25 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes ranged from 964 (conducted in Canada) to 2,311,282 (conducted in UK) ( 25 , 26 ). Four studies used the IMD to assess social deprivation ( 22 , 26 , 28 , 29 ), two studies used the ADI ( 19 , 27 ), and five studies used other assessment tools, including the NZDI, HII, PMDI, TDI, and SDI ( 20 , 21 , 23 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…The lower odds of physical activity among those with less than high school education and low income during the pandemic is consistent with previous studies before the pandemic ( Scholes and Bann, 2007 , Kari et al, Jul 2020 , Droomers et al, 2001 , Armstrong et al, 2018 ). Other studies have found increased mortality and morbidity rates among certain racial and ethnic groups, suggesting the need to enhance health-related behaviors like physical activity to reduce racial/ethnic health-related disparities among these populations ( Habibdoust et al, 2022 , Nguyen et al, 2022 , Unruh et al, 2022 , Grosicki et al, 2022 , Walls et al, 2023 ). Furthermore, the significantly lower prevalence in moderate intensity physical activity behavior highlighted in this study among Black, Hispanic, and Asian individuals calls for greater efforts to encourage physical activity among these communities.…”
Section: Discussionmentioning
confidence: 99%
“…Since the onset of the COVID-19 pandemic, research on its implications has steadily increased, with most studies focused on clinical outcomes. Latinos had high rates of COVID-19 contraction (Turner et al , 2020), higher odds of inpatient hospitalization and lower odds of not receiving treatment, compared with non-Latino whites (Walls et al , 2022). Latinos also experienced higher rates of unemployment compared with other groups (Cleveland and Waslin, 2021), with Latina immigrants experiencing the highest unemployment rate at 22% in April 2020 (Capps et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%